The semiotics of cartographic symbols on old maps - Gašperič, Primož; Babič, Saša (Acta geographica Slovenica, 2023)
This study analyzed selected cartographic symbols on old maps depicting the territory of Slovenia from the sixteenth to nineteenth century. A semiotic approach was applied to establish connections between cartographic symbols on old maps and the characteristics of society at the time the maps were created. This semiotic approach was used to discuss the impact of the interpretation of four symbolic cartographic elements, their iconic basis, and the reading of the five maps analyzed. Cartographic symbols changed in line with the development of cartography at the time, as well as society. The depictions of settlements were first stylistic and then geometric. Relief depictions were first stylized and then shown through plastic or spatial methods. Cartographic symbols gradually changed into symbolic signs (in the semiotic sense), including the quality of the map display, as a result of developments and the demands of changing society.